IMPROVING STUDENTS' MOTIVATION AND SPEAKING ABILITY USING ONLINE MEDIA LEARNING - Ade Onema Septian; Baginda Simaibang; Mulyadi Mulyadi (Universitas PGRI Palembang, 2023)
The objective of this study was to find out and analyze the process of improving students’ motivation and speaking ability of the third year students package C of SPNF SKB Kab,. OKU by using WhatsApp Application. The method which used in this research is classroom action research where the researcher works together with the collaborator/other English teacher. This research was carried out by following Kemmis & Taggart action research procedure where it took place in 3 cycles. The result of this study found that there was improvement of students' speaking ability and motivation. The score of minimum completeness criteria of English lesson was 70. Finding in cycle 1 there were 15 students who pass the minimum completeness criteria or 50 % of students. Finding test in cycle 2 there were 20 students who pass the minimum completeness criteria or 66% of students and than the finding in cycle 3 there were 26 students who pass the minimum completeness criteria or 86% of students. There were improvement of students speaking ability from cycle 1 to cycle 2 gained improvement as 16% and from cycle 2 to cycle 3 gained improvement as 20%. The students' participation increased during the teaching learning process whereas it indicates the students' motivation had increased. Utami (2020) have researched about WhatsApp Application in blended learning where she found that WhatsApp application effective to use as a learning media in writing descriptive text and now the researcher found that WhatsApp application can use as a learning media to improve students’ motivation and students' speaking ability.